Robust, highly customizable, and economical multi-channel electrode for chronic multi-unit recording in behaving animals. (December 2017) - Tateyama, Yukina; Oyama, Kei; Shiraishi, Masaru; Iijima, Toshio; Tsutsui, Ken-Ichiro
Highlights: We developed a novel multi-channel electrode with sufficient physical strength. The electrode consisted of economical materials and is easily fabricated. The electrode could be used for 3–4 times even without removing the dura mater. The electrode would be a useful tool for chronic recording at a low cost. Abstract: Multi-unit recording has been one of the most widely used techniques to investigate the correlation between multiple neuronal activities and behavior. However, a common problem of currently used multi-channel electrodes is their physical weakness. In this study, we developed a novel multi-channel electrode with sufficient physical strength to penetrate a thickened dura mater. This electrode consists of low-cost materials and is easily fabricated, and it enables recording without removing dura mater, thereby reducing the risk of inflammation, infection, or brain herniation. The low-cost multi-channel electrode developed in this study would be a useful tool for chronic recording in behaving animals.